Anticancer effect of the IgY that produced against a small peptide with 15 amino acids of human DR5 on MCF7 cell line - Amirijavid, Shaghayegh; Hashemi, Mehrdad; Akbarzadeh, Azim; Parivar, Kazem; Khakpoor, Mansoor (Archives of Advances in Biosciences, 2013)
Tumor necrosis factor- α (TNF-α) plays an important role in diverse cellular events such as septic shock, induction of other cytokines, cell proliferation and apoptosis. Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is currently attracting great interest as a potential anticancer drug. TRAIL could selectively induce apoptosis in tumor cells in vitro and in vivo by a death receptor-mediated process. TRAIL shows a high degree of promiscuity as it binds to the DR5 receptor and it is generating considerable interests as a possible anticancer therapeutic agent. Use of TRAIL or its antagonist could be a good anticancer treatment in future. The extracellular domain of DR5 human protein which has the attachment part of this ligand to TRAIL ligand is considerable domain of it. We produced a small peptide with just 15 aminoacids from this domain, with peptide synthesizer. Then inject them to hens to immunize them and achieve high affinity IgY. At least, obtained IgYs specially recognize DR5 protein and in vitro start exclusively to induce death in the MCF7 cell line, and interestingly not on normal cells.